Science: Estonia sells its gene pool: A genetic database project is an ethical timebomb - Gross, Michael (The Guardian (London), 2000)
Each living person has a large number of genetic traits, such as eye colour, body shape and inherited abilities or disabilities, which cannot be easily related to the genetic markers. So far, only relatively rare medical conditions have been successfully matched with genetic markers. While a collection of genetic, genealogical or medical data would be relatively harmless, the connections between the three contain ethical timebombs of different kinds. The database may contain evidence proving that tens of thousands of people are not related to the man they consider to be their father. Anybody hacking into the data should find a rich supply of people to blackmail. Similarly, other information could be of sufficient value to some to encourage illegal access and use of the data. Simply replacing the subjects' names with codes and making a law to say that the misuse of genetic data is forbidden will not be sufficient to protect the privacy of the research subjects. While the ethical dilemmas surrounding genetic screening have been debated at length in Britain and other European countries, Estonians don't seem to be aware of these problems. The Weekly Crier, a web news service from the Baltic countries, cites a medical professor, Tiina Tasmuth, one of the few critics of the project as saying: "People here don't ask why, as they do in the west." If they did, the honest answer would probably be most likely to sound like "money". After all, the investors who will eventually fund the project will want something in return, such as patents on new genetic tests, the uses and misuses of which we can't even imagine today.